Trois théories antiques de la divination: Plutarque, Jamblique, Augustin - Timotin, Andrei (Ancient philosophy & religion, 2022)
"This book examines three authors - Plutarch, Iamblichus and Augustine - who deeply impacted the ancient philosophical debates about divination. The author highlights the coherence of ancient theories about divination, the importance of the Platonic heritage in this intellectual history, its dialogue with other philosophical schools (e.g., the Peripatetics and Stoa), and its echoes in Patristic thought. This book thus sheds light on an essential but relatively neglected aspect of the relationship between philosophy and religion in Antiquity. Ce livre examine trois auteurs - Plutarque, Jamblique et Augustin - qui ont marqué les débats philosophiques sur la divination dans l'Antiquité. L'auteur met en évidence la cohérence de la pensée antique relative à la divination, l'importance de l'héritage platonicien dans cette histoire intellectuelle, son dialogue avec d'autres courants philosophiques (e.g. l'aristotélisme et le stoïcisme) et sa postérité dans la pensée patristique. Ce livre contribue ainsi à éclairer un aspect essentiel mais relativement négligé des rapports entre philosophie et religion dans l'Antiquité"--